ZAKAT PRODUKTIF SEBAGAI SOLUSI ALTERNATIF PENGENTASAN KEMISKINAN - ., Amirah (PERMANA, 2011)
Poverty is one of the serious economic problems being faced by many developing countries. This phenomenon is not only an economic problem but also a social and political problems of a country. Since the 14th century, zakat is one of the instruments that are considered able to cope with the economic crisis. In implementation, zakat is not only limited to pillars of Islam, but it has a domino effect in people´s lives, especially in elevating poverty. in addition, the application of zakat can improve economic and social growth. Where theoretically, the allocation of zakat to the poor people will increase their income and consumption. It does not only result in increased production and investment, and demand for labor. Thus, as the unemployment plague the social crisis can be solved.